Indonesia’s First Spaceport Plan in Biak Island: A View from International Relations - Korwa, Johni R.V.; Sinaga, Melpayanty; Renyoet, Claudia Conchita; Amenes, Apriani Anastasia; Darwis, Danial (Jurnal Hubungan Internasional, 2024)
This study critically examined Indonesia’s first spaceport plan in Biak Island against the Indonesian Government’s underlying objective of bolstering the country’s position to become the regional power in Southeast Asia. By using three analytical frameworks proposed by Destradi (empire, hegemony, and leadership), this study claimed that the building of the Biak spaceport could represent the extension of Indonesia’s political control and domination in Southeast Asia. If built, the spaceport would also be the beginning of an empire in spaceport use. By forging international partnerships with those interested in spaceport services in Southeast Asia and outside the region, Indonesia could gain soft power and be seen as a benevolent hegemony. Indonesia has previously demonstrated a proven track record of success in the launch of the PALAPA satellite, which became the first instrument employed by all ASEAN countries in 1976. Thus, constructing the Biak spaceport could possibly revive Indonesia’s leadership in Southeast Asia.